2018
DOI: 10.3389/fnins.2018.00520
|View full text |Cite
|
Sign up to set email alerts
|

The Adenosinergic Signaling: A Complex but Promising Therapeutic Target for Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disorder in elderly people. AD is characterized by a progressive cognitive decline and it is neuropathologically defined by two hallmarks: extracellular deposits of aggregated β-amyloid (Aβ) peptides and intraneuronal fibrillar aggregates of hyper- and abnormally phosphorylated Tau proteins. AD results from multiple genetic and environmental risk factors. Epidemiological studies reported beneficial effects of caffeine, a non-selective adenosine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 117 publications
0
21
2
Order By: Relevance
“…Moreover, it has been demonstrated that interaction between cholinergic and glutamatergic transmission is involved in Ca 2+ -dependent neuroprotection [ 56 ]. The glutamatergic system is controlled by various mediators, including adenosine and ACh [ 56 , 57 , 58 ]. In AD, there is a decrease in the number of the N-methyl-D-aspartate (NMDA) receptors resulting in an imbalance between synaptic and extrasynaptic NMDA receptors [ 59 , 60 ].…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%
“…Moreover, it has been demonstrated that interaction between cholinergic and glutamatergic transmission is involved in Ca 2+ -dependent neuroprotection [ 56 ]. The glutamatergic system is controlled by various mediators, including adenosine and ACh [ 56 , 57 , 58 ]. In AD, there is a decrease in the number of the N-methyl-D-aspartate (NMDA) receptors resulting in an imbalance between synaptic and extrasynaptic NMDA receptors [ 59 , 60 ].…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%
“…There is also an epidemiological inverse correlation of caffeine ingestion with Alzheimer's disease (AD) (Cellai et al, 2018;Cunha, 2016).…”
Section: Naturally Occurring Alkylxanthines As the Prototypical Adenosine Receptor Antagonists And Their Therapeutic Usementioning
confidence: 99%
“…It modulates neuronal plasticity (Sebastiao and Ribeiro, 2015), astrocytic activity (Agostinho et al, 2020), learning and memory (Chen, 2014;Simoes et al, 2016;Bannon et al, 2017;Perrier et al, 2019;Temido-Ferreira et al, 2019;Zhang et al, 2020), food intake (Kola, 2008), motor function (Mori, 2020), sleep/wake cycle (Donlea et al, 2017;Lazarus et al, 2019), pain (Vincenzi et al, 2020), immunosupression (Vijayan et al, 2017), proliferation (Jacobson et al, 2019), and aging (Costenla et al, 2011). Adenosine is involved in ischemia and stroke (Williams-Karnesky and Stenzel-Poore, 2009;Melani et al, 2014;Pereira-Figueiredo et al, 2021), epilepsy (Boison and Jarvis, 2020;Tescarollo et al, 2020), and neurodegenerative pathologies such as Parkinson's disease (PD) (Fredholm and Svenningsson, 2020;Glaser et al, 2020), Alzheimer's disease (AD) (Rahman, 2009;Cunha and Agostinho, 2010;Cellai et al, 2018), amyotrophic lateral sclerosis (ALS) (Ng et al, 2015;Sebastiao et al, 2018), and Huntington's disease (HD) (Lee and Chern, 2014). Extracellular adenosine, interacting with P1 receptors (A1R, A2AR, A2BR, and A3R) regulates metabolism through different signaling pathways.…”
Section: Introductionmentioning
confidence: 99%